PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY BERBANTU ALAT PERAGA - Lia Kurnia Sari; Slamet; Benny Hendriana (Prosiding Seminar Nasional Berseri, 2020)
This research aims to improve a students’ mathematical learning outcomes at Junior High School 36 Bekasi, involving 38 students. This research was Classroom Action Research (CAR) consists of 2 cycles. The technique of data collecting used test of students and observation. The pre cycle data were the latest exam result with mean 48,97. The results show that there is an increase in the first and second cycles with the average values are 68 and 78,12. In addition, the percentage of students’ passing the minimum criteria of mastery learning was increasing with 28, 94% in pre cycle, 47,36% on first cycle and 86,21% on second cycle. Teacher activity in the first cycle is 78,47% and in the second cycle is 85,96%. Students activity in the first cycle is 73, 5% and in the second cycle is 93,12%. Thus it can be concluded that Two Stay Two Stray learning model is able to improve the mathematics learning outcomes at Junior High School 36 Bekasi